EVALUATION OF SOIL EROSION AND SUSCEPTIBILITY TO LANDSLIDE MANIFESTATION AS A CONSEQUENCE OF WILDFIRE EVENTS AFFECTED THE ZACHARO MUNICIPALITY, PELOPONNESUS, GREECE - Rozos, D.; Lykoudi, E.; Tsangaratos, P.; Markantonis, K.; Georgiadis, P.; Rondoyanni, Th.; Leivaditi, A.; Kyrousis, I. (Bulletin of the Geological Society of Greece, 2010)
In August 2007, a wildfire affected an area of approximately 135.000m2 in the Municipality of Zacharo, located in Southern Greece at the Peloponnesus peninsula, causing the loss of 41 human lives, and having a dramatic impact on both ecology and economic-social welfare. The present study applies a simplified model for the evaluation of soil erosion and the susceptibility to landslide manifestation on the hydrological basins of the Zacharo Municipality, as consequence of wildfire. The methodology was based on the evaluation and analysis of territorial parameters such as lithology, geomorphology, hydrography and land cover, which are thought to be directly or indirectly related to soil erosion. The final product was a series of hazardous maps showing pre and post-fire soil erosion. An almost double increase in the post-fire area of high vulnerability was identified, covering 48% of the total area, and affecting dramatically the nearby communities. The outcome of this study helped the local and prefectural authorities to address certain mitigating measures in order to face the disastrous consequences of post-fire soil erosion